The role of information in different bargaining protocols - Rafael Hortala-Vallve; Aniol Llorente-Saguer; Rosemarie Nagel (Max Planck Institute for Research on Collective Goods, 2012)
We analyze a bargaining protocol recently proposed in the literature vis-à-vis unconstrained negotiation. This new mechanism extracts gains from trade inherent in the differing valuation of two parties towards various issues where conflict exists. We assess the role of incomplete vs. complete information in the efficiency achieved by this new mechanism and by unconstrained negotiation. We find that unconstrained negotiation does best under a situation of complete information where the valuations of both bargaining parties are common knowledge. Instead, the newly proposed mechanism does best in a situation with incomplete information. The sources of inefficiencies in each of the two cases arise from the different strategic use of the available information.
Keywords: 330; Verhandlungstheorie; Information; Unvollkommene Information; Konfliktregelung; Theorie